HUINCUL KIMVN. LOOKING AT HISTORY “FROM ABOVE” - Canales Tapia, Pedro (Revista de Historia Social y de las Mentalidades, 2013)
The following work is a proposition regional historical, ethnographic character, which covered the techniques and proposals emanating from the oral history and memory studies, provide a description of the life situation of two elderly Mapuche. This story shows, from orality of the subjects, the connection and conflict decoupling between life history and national history - hegemonic, accounting and impoverished marginal seat that the Mapuche population undergoes structurally from loss its territory and dismantle it in the nineteenth century. Thus, the story revolves Mapuche from memory devices and their link with otherness, from positions marked by the coloniality of social relations among themselves and with others / as. Rescue, then the historical memory of two elderly Mapuche us into the discussion about the ongoing construction of ethnic identity and ethnicity deployment among members of a particular group, there discourses emerging from cultural, political and social demands, which interpellate colonizing and hegemonic society, from areas as diverse as the ritual, the environment and the relationship man - nature.